KINERJA GURU BERBASIS GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH, PELATIHAN GURU DAN BUDAYA ORGANISASI (STUDI EMPIRIS PADA SEKOLAH DASAR NEGERI DI DAERAH KECAMATAN SERPONG KOTA TANGERANG SELATAN) - Putri Melynia Kusuma Dewi; Zubaidah, Siti; Anwar, Saiful Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the influence of principals’ transformational leadership, teacher training, and organizational culture on teacher performance in public elementary schools located in Serpong District, South Tangerang City. The study employed a quantitative approach using a survey method. The research population consisted of 160 teachers from public elementary schools in the Serpong District, with a sample of 114 teachers selected using an appropriate sampling technique. Data were collected through questionnaires that had been tested for validity and reliability. The data were analyzed using multiple linear regression analysis to determine the partial and simultaneous effects of the independent variables on teacher performance. The results indicate that principals’ transformational leadership, teacher training, and organizational culture have a positive and significant effect on teacher performance, both partially and simultaneously. These findings suggest that improving teacher performance can be achieved through strengthening transformational leadership practices, implementing continuous teacher training programs, and fostering a supportive school organizational culture. This study is expected to contribute theoretically to the development of educational management studies and provide practical implications for improving the quality of basic education.